Choice of an Exchange-Rate Arrangement, Institutional Setting and Inflation Empirical Evidence From Latin America - Freytag, Andreas (OECD Development Centre Working Papers, 2002)
The debate about whether fixed or flexible exchange-rate regimes are better suited to guaranteeing stability has received added stimulus from the macroeconomic crisis in Argentina. This paper argues that it is misleading solely to concentrate on exchange-rate policy to assess the preconditions for stability in an international surrounding. Instead, the exchange-rate regime and the institutional setting have to be compatible to increase the former's credibility and to contribute to stability. This hypothesis is empirically tested for Latin American countries. The exchange-rate regime and the institutional setting are linked to form an ex ante proxy for the credibility of the exchange-rate arrangement. We specify the exchange-rate regimes and institutions in Latin America from 1975 to the late 1990s prior to an empirical assessment of the hypothesis. Finally, the Argentine case is discussed specifically. Policy conclusions round off the paper ...